Pengaruh Self-Determination Theory dan Kepercayaan Pengguna terhadap Niat Adopsi AI ChatGPT dengan Karakteristik Teknologi sebagai Variabel Mediasi - Rayyan, Adnin Canina; Susilowati, Nurdian (Jurnal EMT KITA, 2026)
The use of AI ChatGPT is increasing in higher education environments. This study aims to analyze the influence of SELF-Determination Theory, which includes Perceived Autonomy, Perceived Competence, and Perceived Relatedness, as well as user trust, on the adoption intention of AI ChatGPT, with Technology Characteristics as a mediating variable. The research sample consisted of 117 Accounting Education students from the 2023 intake who were selected using probability sampling techniques. The research method used was a quantitative approach with Structural Equation Modeling analysis based on Partial Least Squares (SEM - PLS). The results showed that Self-Determination Theory and user trust had a positive effect on the adoption intention of AI ChatGPT and acted as mediating variables in the relationship between the independent variables and adoption intention. The conclusion of this study confirms that fulfilling psychological needs, user trust, and technology characteristics need to be considered to encourage optimal adoption of AI ChatGPT in the education sector.